The rules of wealth : a personal code for prosperity and plenty - Templar, Richard, 1950-2006 (Pearson, 2023)
"The Rules to Wealth are the guiding principles that will help you generate more money, handle it more wisely, grow it more effectively, and use it to live a happier, more fulfilling and comfortable life"--